Dynamic covalent bond cross-linked I-PDMS / DEA (at) alpha-ZrP-SH self-repairing anti-friction super-hydrophobic anticorrosive paint and preparation method and coating thereof
Through dynamic covalent bond crosslinking I-PDMS/DEA@α-ZrP-SH coating, the existing superhydrophobic anti-corrosion coating has been solved, and the performance of the existing superhydrophobic anti-corrosion coating is reduced in mechanical friction and harsh environments is achieved, and the coating is self-repair and friction resistance is maintained, superhydrophobic performance is improved and the corrosion resistance is improved.
Patent Information
- Application Number
- CN202510089122.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-21
AI Technical Summary
The existing superhydrophobic anticorrosion coating has reduced superhydrophobic performance, low anticorrosion efficiency, and difficult to self-repair under mechanical friction and harsh environments.
Using dynamic covalent bond crosslinked I-PDMS/DEA@α-ZrP-SH coating, α-ZrP nanosheets were prepared by hydrothermal reaction, and the dispersion of the filler was improved by small molecule amine intercalation to form a solid layered rough structure.
The self-healing ability and friction resistance of the coating are achieved, superhydrophobic properties are maintained, the service life of the coating is extended, and the anti-corrosion efficiency is improved.
Smart Images

Figure CN119799158A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of anti-corrosion coatings, and in particular to a dynamically covalently cross-linked I-PDMS / DEA@α-ZrP-SH self-repairing anti-friction super-hydrophobic anti-corrosion coating, and a preparation method and coating thereof. Background Art
[0002] Superhydrophobic coatings can keep metal surfaces non-wettable and achieve corrosion protection by reducing the interaction between the metal surface and corrosive media in water. Many aquatic animals and plants have superhydrophobic surfaces that have the ability to self-clean, anti-icing, anti-corrosion and anti-pollution. Studies have pointed out that because the stacked micro-nanostructure of the superhydrophobic surface provides an air layer between the solid surface and the droplets, reducing the actual contact area, the high air / solid ratio of the layered structure surface directly leads to the rolling of the droplets, and the low surface energy materials and micro / nanoscale layered structures work together to produce superhydrophobic surfaces. These studies have also been shown to be applicable to the design of artificial surfaces.
[0003] Traditional super-hydrophobic coatings are constructed by embedding nanoparticles into a coating substrate to construct a rough surface, and using low surface energy materials to modify the rough structure to achieve super-hydrophobicity. After the traditional coating is subjected to continuous friction or impact, the nanoparticles are worn off, and defects appear in the rough structure, resulting in a decrease in super-hydrophobicity; when the traditional coating works in a harsh environment (acid-base solution or organic solvent washing, ultraviolet radiation, high temperature, etc.), the surface functional groups change or the hydrophobic long chains decompose, and the super-hydrophobicity also decreases. Therefore, the existing super-hydrophobic anti-corrosion coatings still need to be improved to meet the needs of harsh working environments.
[0004] Traditional superhydrophobic coatings have poor ductility and relaxivity, and are difficult to recover after deformation. Dynamic covalent bonds are strong covalent bonds that can be continuously formed and broken without side reactions, and have attracted attention in the synthesis and design of polymer networks with adaptability and dynamic properties. During the formation of the polymer network, the reversibility of these bonds produces dynamic behaviors of the network, such as self-healing, ductility, and recyclability, which can meet the design requirements of self-healing anti-friction superhydrophobic coatings. Imine bonds are a type of dynamic covalent bonds that can be obtained by the reaction of aldehyde groups and amino groups under mild conditions, with a bond dissociation energy of 147 kcal·mol -1 , polymer materials composed of imine bond cross-linking show excellent mechanical properties. However, the single dynamic covalent bond polymer network has low anti-corrosion efficiency, and there are pores inside during the formation process, which cannot form a dense coating and has poor friction resistance; the coating surface is easily contaminated with dirt and cannot be used alone as a self-cleaning anti-corrosion coating. It is necessary to make up for the defects inside the coating and improve the anti-corrosion efficiency. Summary of the invention
[0005] The technical problems to be solved by the present invention are:
[0006] In the prior art, superhydrophobic anti-corrosion coatings often lose their superhydrophobic performance and have low anti-corrosion efficiency due to mechanical friction and harsh working environment, or are damaged when impacted, thereby rendering their anti-corrosion capabilities ineffective.
[0007] The present invention adopts the following technical solutions to solve the above technical problems:
[0008] The present invention provides a method for preparing a dynamic covalently cross-linked I-PDMS / DEA@α-ZrP-SH self-repairing anti-friction super-hydrophobic anti-corrosion coating, comprising the following steps:
[0009] (1) using zirconium oxychloride octahydrate and phosphoric acid solution as raw materials, and performing a hydrothermal reaction to prepare α-ZrP nanosheets; adding the α-ZrP nanosheets into an organic solvent to prepare an α-ZrP suspension, and slowly adding diethanolamine to the α-ZrP suspension, ultrasonicating, and stirring to intercalate diethanolamine (DEA) into the α-ZrP, thereby preparing DEA@α-ZrP;
[0010] (2) dispersing DEA@α-ZrP in organic solvent 2 to obtain a DEA@α-ZrP suspension, adding n-dodecyl mercaptan to the DEA@α-ZrP suspension, and allowing the n-dodecyl mercaptan to be grafted onto the surface of DEA@α-ZrP to obtain DEA@α-ZrP-SH nanosheets;
[0011] (3) Polydimethylsiloxane (PDMS) was used as the coating substrate and diluted, and trimesic acid (BTC) was added and mixed evenly to obtain an I-PDMS dilution solution. DEA@α-ZrP-SH nanosheets were then added to the I-PDMS dilution solution, and ultrasonication was performed to uniformly disperse them. Finally, a curing agent was added to obtain an I-PDMS / DEA@α-ZrP-SH self-cleaning thermal conductive anti-corrosion coating.
[0012] Furthermore, the hydrothermal reaction temperature in step (1) is 150-300°C.
[0013] Furthermore, in step (1), the concentration of the phosphoric acid solution is 9 M, and the ratio of the phosphoric acid solution to zirconium oxychloride octahydrate is 40 ml: 3.5-5 g.
[0014] Furthermore, in step (1), the first organic solvent is acetone, and the ratio of α-ZrP, acetone and diethanolamine is 1 g: 100 ml: (1.5-3) mL.
[0015] Furthermore, in step (1), the ultrasonication time is 1 to 4 hours, and the stirring time is 2 to 5 hours.
[0016] Furthermore, in step (2), the second organic solvent is ethanol, and the ratio of DEA@α-ZrP, ethanol and n-dodecyl mercaptan is: 1 g: 40 ml: (0.645-1.146) g.
[0017] Furthermore, the standing time in step 2 is 2 to 5 hours to allow n-dodecyl mercaptan to be grafted onto the surface of DEA@α-ZrP.
[0018] Furthermore, in step (3), polydimethylsiloxane is diluted with tetrahydrofuran, and the ratio of polydimethylsiloxane, tetrahydrofuran dilution, trimesaldehyde and DEA@α-ZrP-SH is: 0.8 g: 7 mL: (0.025-0.01) g: (0.5-2) g.
[0019] The present invention also provides a dynamically covalently cross-linked I-PDMS / DEA@α-ZrP-SH self-repairing anti-friction super-hydrophobic anti-corrosion coating, which is prepared by the method described in any one of the above technical solutions.
[0020] The present invention also provides a self-repairing anti-friction super-hydrophobic anti-corrosion coating, wherein the anti-corrosion coating is formed by the anti-corrosion coating described in the above technical solution.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The DEA@α-ZrP-SH nanosheets in the invention peel off the α-ZrP layered structure by small molecule amine intercalation to improve the dispersibility of the filler. During the coating formation process, the DEA@α-ZrP-SH nanosheets form a solid layered rough structure through van der Waals force stacking. At the same time, due to the dynamic characteristics of the I-PDMS cross-linked network, when the super-hydrophobic performance decreases due to friction, the coating can quickly restore the super-hydrophobic performance. The I-PDMS / DEA@α-ZrP-SH coating of the present invention has dynamic characteristics. There are free amine groups and aldehyde groups inside the coating. After the long-chain substances on the surface decompose, driven by the minimization of free energy, the free amine groups and aldehyde groups diffuse to the damaged parts and spontaneously reorganize to maintain the original low surface energy.
[0023] The I-PDMS / DEA@α-ZrP-SH self-healing super-hydrophobic anti-friction anti-corrosion coating of the present invention is applied to the surface of the equipment to form a coating. On the one hand, DEA@α-ZrP-SH forms a micro-column structure on the surface of I-PDMS, and the coating can achieve self-cleaning, and the surface is not easy to adhere to dirt and ice, and at the same time has a good anti-corrosion effect; on the other hand, the self-healing ability and anti-friction ability of the I-PDMS / DEA@α-ZrP-SH coating can effectively extend the service life of the coating under mechanical friction and harsh environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1: is the infrared spectra of α-ZrP, DEA@α-ZrP and DEA@α-ZrP-SH in the examples of the present invention;
[0025] Figure 2 : is the hydrogen nuclear magnetic resonance spectrum of PDMS and I-PDMS in the embodiments of the present invention;
[0026] Figure 3 is a SEM image of the coating in an embodiment of the present invention;
[0027] Figure 4 This is an AFM scan image of the coating in an embodiment of the present invention;
[0028] Figure 5 The coating photos and water contact angle photos in the embodiments of the present invention are shown in FIG.
[0029] Figure 6 The coating self-repair test results in the embodiment of the present invention are Figure 1 ;
[0030] Figure 7 The coating self-repair test results in the embodiment of the present invention are Figure 2 . DETAILED DESCRIPTION
[0031] In order to enable those skilled in the art to better understand the scheme of the present invention, exemplary implementations or embodiments of the present invention will be described below in conjunction with the accompanying drawings. Obviously, the described implementations or embodiments are only implementations or embodiments of a part of the present invention, not all of them. Based on the implementations or embodiments of the present invention, all other implementations or embodiments obtained by ordinary technicians in the field without creative work should fall within the scope of protection of the present invention.
[0032] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0033] In a typical embodiment of the present invention, a method for preparing a dynamic covalently cross-linked I-PDMS / DEA@α-ZrP-SH self-repairing anti-friction super-hydrophobic anti-corrosion coating is provided, comprising the following steps:
[0034] (1) using zirconium oxychloride octahydrate and phosphoric acid solution as raw materials, and performing a hydrothermal reaction to prepare α-ZrP nanosheets; adding the α-ZrP nanosheets into an organic solvent to prepare an α-ZrP suspension, and slowly adding diethanolamine to the α-ZrP suspension, ultrasonicating, and stirring to intercalate diethanolamine (DEA) into the α-ZrP, thereby preparing DEA@α-ZrP;
[0035] (2) dispersing DEA@α-ZrP in organic solvent 2 to obtain a DEA@α-ZrP suspension, adding n-dodecyl mercaptan to the DEA@α-ZrP suspension, and allowing the n-dodecyl mercaptan to be grafted onto the surface of DEA@α-ZrP to obtain DEA@α-ZrP-SH nanosheets;
[0036] (3) Polydimethylsiloxane (PDMS) was used as the coating substrate and diluted, and trimesic acid (BTC) was added and mixed evenly to obtain an I-PDMS dilution solution. DEA@α-ZrP-SH nanosheets were then added to the I-PDMS dilution solution, and ultrasonic treatment was performed to uniformly disperse them. Finally, a curing agent was added to obtain an I-PDMS / DEA@α-ZrP-SH self-cleaning anti-corrosion coating.
[0037] In a typical embodiment of the present invention, the hydrothermal reaction temperature in step (1) is preferably 150-300°C. During the hydrothermal preparation of α-ZrP, the reaction temperature has a significant effect on the aspect ratio of the sheet. When the aspect ratio of α-ZrP is too large, a sharper rough structure can be obtained, which is conducive to the formation of super-hydrophobic surface micromorphology, but the surface structural stability of the coating will be weakened, and the labyrinth effect inside the coating will be weakened, resulting in a decrease in corrosion resistance. When the aspect ratio is too low, the specific surface area of the nanosheet becomes larger, the interlayer van der Waals force becomes stronger, and it is difficult to disperse. In this embodiment, the inventors have conducted a large number of experiments and preferably the hydrothermal reaction temperature is 150-300°C.
[0038] In a typical embodiment of the present invention, the concentration of the phosphoric acid solution in step (1) is preferably 9M, and the ratio of the phosphoric acid solution to zirconium oxychloride octahydrate is preferably 40ml:3.5-5g. The concentration of the phosphoric acid solution during the hydrothermal preparation of α-ZrP will affect the crystalline structure of α-ZrP. In this embodiment, the inventors have conducted a large number of experiments and preferably the concentration of the phosphoric acid solution is 9M.
[0039] In a typical embodiment of the present invention, since diethanolamine is easily mixed in acetone to form a uniform dilution solution, the intercalation process is uniform, and the organic solvent in step (1) is preferably acetone, and the ratio of α-ZrP, acetone and diethanolamine is preferably 1g:100ml:(1.5-3)mL. In this embodiment, the inventors determined the preferred ratio of α-ZrP, acetone and diethanolamine through a large number of experiments.
[0040] In a typical embodiment of the present invention, in step (1), the ultrasonication time is preferably 1 to 4 hours, and the stirring time is preferably 2 to 5 hours.
[0041] In a typical embodiment of the present invention, since n-dodecyl mercaptan has good solubility in ethanol and α-ZrP can form a suspension in ethanol, the grafting effect is good. In step (2), the second organic solvent is preferably ethanol, and the ratio of DEA@α-ZrP, ethanol and n-dodecyl mercaptan is preferably: 1g:40ml:(0.645-1.146)g.
[0042] In a typical embodiment of the present invention, the standing time in step 2 is preferably 2 to 5 hours to allow n-dodecyl mercaptan to be grafted onto the surface of DEA@α-ZrP.
[0043] In a typical embodiment of the present invention, since tetrahydrofuran is easily volatile at room temperature, it has good compatibility with the nanosheets as a PDMS diluent, so that the coating is mixed evenly and the formed coating is not prone to defects; in step (3), tetrahydrofuran is preferably used to dilute polydimethylsiloxane, and the ratio of polydimethylsiloxane, tetrahydrofuran dilution, trimesaldehyde and DEA@α-ZrP-SH is preferably: 0.8g:7mL:(0.025~0.01)g:(0.5~2)g.
[0044] The beneficial effects of the present application will be described below in conjunction with specific embodiments and comparative examples.
[0045] Example 1
[0046] (1) Preparation of α-ZrP
[0047] Take 30.55mL of 95wt% phosphoric acid, add 19.45mL of deionized water, stir and mix evenly, then transfer to a 50mL volumetric flask to prepare a 9M phosphoric acid solution; take 40mL of 9M phosphoric acid solution, add 3.5g of ground zirconium oxychloride octahydrate to the phosphoric acid solution, stir and mix evenly, place in a 50mL Teflon-lined reactor and seal, perform hydrothermal reaction at 200°C for 5h, cool to room temperature, take out the product, wash and centrifuge, vacuum dry at 60°C, and grind to obtain pure layered α-ZrP.
[0048] Preparation of DEA@α-ZrP
[0049] 1 g of α-ZrP was added to 100 mL of acetone, stirred and mixed evenly, and then ultrasonically treated to obtain an α-ZrP acetone suspension. Under ultrasonic conditions, 1.5 mL of diethanolamine was added dropwise to the α-ZrP acetone suspension, and ultrasonication was continued for 1 hour. Then, the reaction was stirred at room temperature for 5 hours until the reaction was fully reacted. After the reaction was completed, the mixture was centrifuged at 5000 r / min, washed repeatedly with ethanol for 3 times, and vacuum dried and ground at 60°C to obtain DEA@α-ZrP.
[0050] (2) Preparation of DEA@α-ZrP-SH
[0051] Weigh 1 g of DEA@α-ZrP and place it in a beaker. Add 40 mL of ethanol as a solvent and ultrasonically disperse it for 10 minutes to obtain a DEA@α-ZrP ethanol suspension. Add 0.645 g of n-dodecyl mercaptan to the DEA@α-ZrP ethanol suspension, stir and mix evenly, and let it stand for 3 hours to allow n-dodecyl mercaptan to be grafted onto the surface of DEA@α-ZrP. After the reaction is completed, centrifuge at 5000 rpm, wash repeatedly with ethanol and centrifuge for 3 times, dry at 70°C, and grind to obtain DEA@α-ZrP-SH nanosheets.
[0052] (3) Preparation of self-cleaning anti-corrosion coating
[0053] 7 mL of tetrahydrofuran was added to 0.8 g of polydimethylsiloxane, and the mixture was stirred evenly by magnetic force to obtain a diluted solution of polydimethylsiloxane. 0.02 g of trimesaldehyde was added to the diluted solution of polydimethylsiloxane, and the mixture was ultrasonically treated for 25 min to prepare I-PDMS. 0.5 g of DEA@α-ZrP-SH nanosheets were added to I-PDMS, and the mixture was stirred and mixed again. The mixture was ultrasonically treated for 10 min to uniformly disperse the nanosheets in the diluted solution of I-PDMS to obtain a self-cleaning anticorrosive emulsion. 0.08 g of Dow Corning sylgard184 curing agent was added, and the mixture was stirred and mixed for 10 min to obtain an I-PDMS / DEA@α-ZrP-SH coating.
[0054] Example 2
[0055] The difference between this embodiment and embodiment 1 is that:
[0056] In the preparation of α-ZrP in step (1), 4 g of ground zirconium oxychloride octahydrate was added to the phosphoric acid solution. In the preparation of DEA@α-ZrP, 2 mL of diethanolamine was added dropwise to the α-ZrP acetone suspension.
[0057] Example 3
[0058] The difference between this embodiment and embodiment 1 is that:
[0059] In the preparation of α-ZrP in step (1), 4.5 g of ground zirconium oxychloride octahydrate was added to the phosphoric acid solution. In the preparation of DEA@α-ZrP, 2.5 mL of diethanolamine was added dropwise to the α-ZrP acetone suspension.
[0060] Example 4
[0061] The difference between this embodiment and embodiment 1 is that:
[0062] In the preparation of α-ZrP in step (1), 5 g of ground zirconium oxychloride octahydrate was added to the phosphoric acid solution. In the preparation of DEA@α-ZrP, 3 mL of diethanolamine was added dropwise to the α-ZrP acetone suspension.
[0063] Example 5
[0064] The difference between this embodiment and embodiment 2 is that:
[0065] In step (2), 0.845 g of n-dodecyl mercaptan is added to the DEA@α-ZrP ethanol suspension.
[0066] Example 6
[0067] The difference between this embodiment and embodiment 3 is that:
[0068] In step (2), 0.977 g of n-dodecyl mercaptan is added to the DEA@α-ZrP ethanol suspension.
[0069] Example 7
[0070] The difference between this embodiment and embodiment 4 is that:
[0071] In step (2), 1.146 g of n-dodecyl mercaptan was added to the DEA@α-ZrP ethanol suspension.
[0072] Example 8
[0073] The difference between this embodiment and embodiment 5 is that:
[0074] In step (3), 0.04 g of trimesaldehyde is added to the diluted solution of polydimethylsiloxane.
[0075] Example 9
[0076] The difference between this embodiment and embodiment 6 is that:
[0077] In step (3), 0.06 g of trimesaldehyde is added to the diluted solution of polydimethylsiloxane.
[0078] Example 10
[0079] The difference between this embodiment and embodiment 7 is that:
[0080] In step (3), 0.08 g of trimesaldehyde is added to the diluted solution of polydimethylsiloxane.
[0081] Embodiment 11
[0082] The difference between this embodiment and embodiment 5 is that:
[0083] In the preparation of α-ZrP in step (1), the hydrothermal reaction conditions are: hydrothermal reaction at 150° C. for 5 hours.
[0084] Example 12
[0085] The difference between this embodiment and embodiment 5 is that:
[0086] In the preparation of α-ZrP in step (1), the hydrothermal reaction conditions are: hydrothermal reaction at 250° C. for 5 h.
[0087] Embodiment 13
[0088] The difference between this embodiment and embodiment 5 is that:
[0089] In the preparation of α-ZrP in step (1), the hydrothermal reaction conditions are: hydrothermal reaction at 300° C. for 5 h.
[0090] Embodiment 14
[0091] The difference between this embodiment and embodiment 5 is that:
[0092] Step (1) In the preparation of DEA@α-ZrP, 2 mL of diethanolamine was added dropwise to the α-ZrP acetone suspension, ultrasonicated for 2 h, and stirred at room temperature for 4 h.
[0093] Embodiment 15
[0094] The difference between this embodiment and embodiment 5 is that:
[0095] Step (1) In the preparation of DEA@α-ZrP, 2 mL of diethanolamine was added dropwise to the α-ZrP acetone suspension, and ultrasonication was continued for 3 h, followed by stirring at room temperature for 3 h.
[0096] Example 16
[0097] The difference between this embodiment and embodiment 5 is that:
[0098] Step (1) In the preparation of DEA@α-ZrP, 2 mL of diethanolamine was added dropwise to the α-ZrP acetone suspension, ultrasonicated for 4 h, and stirred at room temperature for 2 h.
[0099] Embodiment 17
[0100] The difference between this embodiment and embodiment 14 is that:
[0101] In step (2), 0.845 g of n-dodecyl mercaptan was added to the DEA@α-ZrP ethanol suspension, the mixture was stirred and mixed evenly, and the mixture was allowed to stand for 2 h to allow n-dodecyl mercaptan to be grafted onto the surface of DEA@α-ZrP.
[0102] Embodiment 18
[0103] The difference between this embodiment and embodiment 14 is that:
[0104] In step (2), 0.845 g of n-dodecyl mercaptan was added to the DEA@α-ZrP ethanol suspension, the mixture was stirred and mixed evenly, and the mixture was allowed to stand for 4 h to allow n-dodecyl mercaptan to be grafted onto the surface of DEA@α-ZrP.
[0105] Embodiment 19
[0106] The difference between this embodiment and embodiment 14 is that:
[0107] In step (2), 0.845 g of n-dodecyl mercaptan was added to the DEA@α-ZrP ethanol suspension, the mixture was stirred and mixed evenly, and the mixture was allowed to stand for 5 h to allow n-dodecyl mercaptan to be grafted onto the surface of DEA@α-ZrP.
[0108] Embodiment 20
[0109] The difference between this embodiment and embodiment 18 is that
[0110] Step (3) Add 2 g of DEA@α-ZrP-SH nanosheets to the I-PDMS, stir and mix again, and ultrasonically treat for 10 min to uniformly disperse the nanosheets in the diluted I-PDMS solution to obtain a self-cleaning antiseptic emulsion.
[0111] Embodiment 21
[0112] The difference between this embodiment and embodiment 18 is that
[0113] Step (3) Add 1.5 g of DEA@α-ZrP-SH nanosheets to the I-PDMS, stir and mix again, and ultrasonically treat for 10 min to uniformly disperse the nanosheets in the diluted I-PDMS solution to obtain a self-cleaning antiseptic emulsion.
[0114] Embodiment 22
[0115] The difference between this embodiment and embodiment 18 is that
[0116] Step (3) adding 1 g of DEA@α-ZrP-SH nanosheets to the I-PDMS, stirring and mixing again, and ultrasonically treating for 10 min to uniformly disperse the nanosheets in the diluted I-PDMS solution to obtain a self-cleaning antiseptic emulsion.
[0117] Comparative Example 1
[0118] (1) Preparation of α-ZrP
[0119] Take 30.55mL of 95wt% phosphoric acid, add 19.45mL of deionized water, stir and mix evenly, then transfer to a 50mL volumetric flask to prepare a 9M phosphoric acid solution; take 40mL of 9M phosphoric acid solution, add 4g of ground zirconium oxychloride octahydrate to the phosphoric acid solution, stir and mix evenly, place in a 50mL Teflon-lined reactor and seal, perform hydrothermal reaction at 200°C for 5h, cool to room temperature, take out the product, wash and centrifuge, vacuum dry at 60°C, and grind to obtain pure layered α-ZrP.
[0120] Preparation of DEA@α-ZrP
[0121] 1 g of α-ZrP was added to 100 mL of acetone, stirred and mixed evenly, and then ultrasonically treated to obtain an α-ZrP acetone suspension. Under ultrasonic conditions, 2 mL of diethanolamine was added dropwise to the α-ZrP acetone suspension, and ultrasonication was continued for 2 h. Then, the reaction was stirred at room temperature for 4 h until sufficient reaction occurred. After the reaction was completed, the mixture was centrifuged at 5000 r / min, washed repeatedly with ethanol for 3 times, and vacuum dried and ground at 60 °C to obtain DEA@α-ZrP.
[0122] (2) Preparation of DEA@α-ZrP-SH
[0123] Weigh 1 g of DEA@α-ZrP and place it in a beaker. Add 40 mL of ethanol as a solvent and ultrasonically disperse it for 10 minutes to obtain a DEA@α-ZrP ethanol suspension. Add 0.845 g of n-dodecyl mercaptan to the DEA@α-ZrP ethanol suspension, stir and mix evenly, and let it stand for 4 hours to allow n-dodecyl mercaptan to be grafted onto the surface of DEA@α-ZrP. After the reaction is completed, centrifuge at 5000 rpm, wash repeatedly with ethanol and centrifuge for 3 times, dry at 70°C, and grind to obtain DEA@α-ZrP-SH nanosheets.
[0124] (3) Preparation of self-cleaning anti-corrosion coating
[0125] Add 7 mL of tetrahydrofuran to 0.8 g of polydimethylsiloxane and stir evenly with a magnetic stirrer to obtain a PDMS diluent; add 1 g of DEA@α-ZrP-SH nanosheets, stir and mix again, and ultrasonically treat for 10 minutes to evenly disperse the nanosheets in the PDMS diluent to obtain a self-cleaning anticorrosive emulsion; add 0.08 g of Dow Corning sylgard184 curing agent, stir and mix for 10 minutes to obtain an I-PDMS / DEA@α-ZrP-SH coating.
[0126] Comparative Example 2
[0127] (1) Preparation of α-ZrP
[0128] Take 30.55mL of 95wt% phosphoric acid, add 19.45mL of deionized water, stir and mix evenly, then transfer to a 50mL volumetric flask to prepare a 9M phosphoric acid solution; take 40mL of 9M phosphoric acid solution, add 4g of ground zirconium oxychloride octahydrate to the phosphoric acid solution, stir and mix evenly, place in a 50mL Teflon-lined reactor and seal, perform hydrothermal reaction at 200°C for 5h, cool to room temperature, take out the product, wash and centrifuge, vacuum dry at 60°C, and grind to obtain pure layered α-ZrP.
[0129] (2) Preparation of self-cleaning anti-corrosion coating
[0130] 7 mL of tetrahydrofuran was added to 0.8 g of polydimethylsiloxane, and the mixture was stirred evenly by magnetic force to obtain a diluted solution of polydimethylsiloxane. 0.02 g of trimesaldehyde was added to the diluted solution of polydimethylsiloxane, and the mixture was ultrasonically treated for 25 min to prepare I-PDMS. 1 g of α-ZrP nanosheets was added to the I-PDMS, and the mixture was stirred and mixed again. The mixture was ultrasonically treated for 10 min to uniformly disperse the nanosheets in the diluted solution of I-PDMS to obtain a self-cleaning anticorrosive emulsion. 0.08 g of Dow Corning sylgard 184 curing agent was added, and the mixture was stirred and mixed for 10 min to obtain an I-PDMS / α-ZrP coating.
[0131] The DEA@α-ZrP-SH / I-PDMS coating prepared in Example 1-22 and the coating of Comparative Example 1-2 were coated on a Q235 steel sheet of 100×60×0.3 mm, transferred to a vacuum drying oven and heated at 70°C for 8 h to evaporate tetrahydrofuran; and aged in a 100°C forced air drying oven for 4 h to obtain a coating.
[0132] Each coating was subjected to a superhydrophobic test: a contact angle meter (Shanghai Xuanzhun Instrument, SZ-CAMB1 contact angle meter) was used to detect the water contact angle (CA) of the coating. 800-mesh sandpaper was cut into a suitable size and placed on the coating. A 200-g weight was placed on the sandpaper and the sandpaper was repeatedly dragged to perform a cyclic friction test. The water contact angle was tested after 50 cycles of friction.
[0133] Prepare 3.5% NaCl solution as electrolyte, use the coated tinplate as working electrode, graphite electrode as auxiliary electrode, and silver chloride electrode as reference electrode to construct a three-electrode system, and analyze the corrosion resistance of the coating by electrochemical workstation
[0134] The α-ZrP, DEA@α-ZrP and DEA@α-ZrP-SH in Example 22 were analyzed. Figure 1 The infrared spectrum analysis results shown in the figure show that at 1460cm -1A new absorption peak appears at 3175cm, indicating the appearance of NH bond; the OH peak in α-ZrP weakens, proving that DEA is successfully introduced into the interlayer of α-ZrP; -1 The peak at 47° becomes broad, indicating the presence of SH bonds. Figure 2 As shown in the figure, the peak a of PDMS and I-PDMS is the ortho-equivalent H of tetrahydrofuran, the peak b is the meta-equivalent hydrogen, and the peak s contains many impurities, mainly including the alkyl equivalent hydrogen on the siloxane molecular chain and the amino-terminated H; in the spectrum of I-PDMS, the characteristic peak of the imine bond H appears at 9.26ppm, indicating that the Schiff base reaction occurred inside the I-PDMS coating to form a dynamic imine bond. Figure 3 The SEM results shown in the figure show that α-ZrP is a regular hexagonal cake-shaped crystal. After being treated with DEA, it forms a thin and dispersed sheet structure. After being treated with n-dodecyl mercaptan, there is no obvious morphological change and the original crystal structure is maintained. Figure 4 The AFM scanning analysis results shown in Table 1 show that there are a large number of micro-column structures on the surface of the DEA@α-ZrP-SH coating. The arithmetic mean deviation (Ra) of the profile is used as the parameter to describe the average surface roughness, and the root mean square deviation (Rq) of the profile is used as the mean square roughness parameter. It can be calculated that Ra = 204.630nm, Rq = 257.242nm. Figure 5 , Figure 6 As shown in Table 2, the static contact angle of the DEA@α-ZrP-SH / I-PDMS coating is 162°. After 250 cycles of friction, the contact angle drops to 150°, and after 600 cycles of friction, it drops to 137°, losing its superhydrophobic properties. After standing at 80°C for 1 hour, the dynamic imine bonds inside the coating spontaneously reorganize, the superhydrophobic effect of the coating is restored, and the contact angle recovers to 159°. The Tafel test results shown in Table 2 show that the electrochemical impedance of the DEA@α-ZrP-SH / I-PDMS coating reaches 74043.19Ω / cm 2 , the corrosion current reaches 1.76×10 - 4 mA / cm 2 , the anti-corrosion effect is good.
[0135] In Comparative Example 1, the filler is DEA@α-ZrP-SH, the coating substrate is PDMS, and after adding the crosslinking agent, heating is performed to form a long-chain stable structure. The crosslinking agent added to PDMS decomposes after heating, releasing free radicals, which are captured by the active silicon groups of polydimethylsiloxane, and a crosslinking reaction occurs. Since there is no imine bond inside the PDMS coating, there is no self-healing function, such as Figure 7As shown. In Comparative Example 2, the coating substrate is I-PDMS, and α-ZrP is selected as the filler. The α-ZrP flakes that have not been intercalated are not dispersed enough, and it is difficult to evenly fill the pores and defects inside the coating, which greatly reduces the anti-corrosion efficiency. The surface energy of α-ZrP nanosheets is higher than that of α-ZrP-SH nanosheets grafted with n-dodecyl mercaptan. At the same time, the α-ZrP flakes are thicker than DEA@α-ZrP, and cannot form a dense and rough structure on the coating surface, resulting in insufficient hydrophobicity of the coating, as shown in Table 2.
[0136] Table 1
[0137]
[0138] Table 2
[0139]
[0140]
[0141] Although the present invention is disclosed as above, the protection scope of the present invention is not limited thereto. Those skilled in the art may make various changes and modifications without departing from the spirit and scope of the present invention, and these changes and modifications will fall within the protection scope of the present invention.
Claims
1. A method for preparing a dynamic covalently cross-linked I-PDMS / DEA@α-ZrP-SH self-repairing anti-friction super-hydrophobic anti-corrosion coating, characterized in that: The steps include: (1) using zirconium oxychloride octahydrate and phosphoric acid solution as raw materials, and performing a hydrothermal reaction to prepare α-ZrP nanosheets; adding the α-ZrP nanosheets into an organic solvent to prepare an α-ZrP suspension, and slowly adding diethanolamine to the α-ZrP suspension, ultrasonicating, and stirring to intercalate diethanolamine (DEA) into the α-ZrP, thereby preparing DEA@α-ZrP; (2) dispersing DEA@α-ZrP in organic solvent 2 to obtain a DEA@α-ZrP suspension, adding n-dodecyl mercaptan to the DEA@α-ZrP suspension, and allowing the n-dodecyl mercaptan to be grafted onto the surface of DEA@α-ZrP to obtain DEA@α-ZrP-SH nanosheets; (3) Polydimethylsiloxane (PDMS) was used as the coating substrate and diluted, and trimesic acid (BTC) was added and mixed evenly to obtain an I-PDMS dilution solution. DEA@α-ZrP-SH nanosheets were then added to the I-PDMS dilution solution, and ultrasonication was performed to uniformly disperse them. Finally, a curing agent was added to obtain an I-PDMS / DEA@α-ZrP-SH self-cleaning thermal conductive anti-corrosion coating.
2. The method for preparing the dynamic covalently cross-linked I-PDMS / DEA@α-ZrP-SH self-repairing anti-friction super-hydrophobic anti-corrosion coating according to claim 1, characterized in that: The hydrothermal reaction temperature in step (1) is 150-300°C.
3. The method for preparing the dynamic covalently cross-linked I-PDMS / DEA@α-ZrP-SH self-repairing anti-friction super-hydrophobic anti-corrosion coating according to claim 2, characterized in that: In step (1), the concentration of the phosphoric acid solution is 9M, and the ratio of the phosphoric acid solution to zirconium oxychloride octahydrate is 40 ml: 3.5-5 g.
4. The method for preparing the I-PDMS / DEA@α-ZrP-SH self-repairing anti-friction super-hydrophobic anti-corrosion coating with dynamic covalent bond cross-linking according to claim 3, characterized in that: In step (1), the first organic solvent is acetone, and the ratio of α-ZrP, acetone and diethanolamine is 1 g: 100 ml: (1.5-3) mL.
5. The method for preparing the I-PDMS / DEA@α-ZrP-SH self-repairing anti-friction super-hydrophobic anti-corrosion coating with dynamic covalent bond cross-linking according to claim 4, characterized in that: In step (1), the ultrasonication time is 1 to 4 hours, and the stirring time is 2 to 5 hours.
6. The method for preparing the I-PDMS / DEA@α-ZrP-SH self-repairing anti-friction super-hydrophobic anti-corrosion coating with dynamic covalent bond cross-linking according to claim 5, characterized in that: In step (2), the second organic solvent is ethanol, and the ratio of DEA@α-ZrP, ethanol and n-dodecyl mercaptan is: 1g:40ml:(0.645-1.146)g.
7. The method for preparing the dynamic covalently cross-linked I-PDMS / DEA@α-ZrP-SH self-repairing anti-friction super-hydrophobic anti-corrosion coating according to claim 6, characterized in that: The standing time in step 2 is 2 to 5 hours to allow n-dodecyl mercaptan to be grafted onto the surface of DEA@α-ZrP.
8. The method for preparing the dynamic covalently cross-linked I-PDMS / DEA@α-ZrP-SH self-repairing anti-friction super-hydrophobic anti-corrosion coating according to claim 7, characterized in that: In step (3), polydimethylsiloxane is diluted with tetrahydrofuran, and the ratio of polydimethylsiloxane, tetrahydrofuran dilution, trimesaldehyde and DEA@α-ZrP-SH is: 0.8 g: 7 mL: (0.025-0.01) g: (0.5-2) g.
9. A dynamic covalently cross-linked I-PDMS / DEA@α-ZrP-SH self-repairing anti-friction super-hydrophobic anti-corrosion coating, characterized in that: Prepared by the method according to any one of claims 1 to 8.
10. A self-repairing anti-friction super-hydrophobic anti-corrosion coating, characterized in that: The anti-corrosion coating is formed by the anti-corrosion paint according to claim 9.
Citation Information
Patent Citations
Method for preparing GO-PDA-CeO2 / PU wear-resistant super-hydrophobic long-acting anti-corrosion coating
CN115820091A
Preparation method and application of water-based metal anticorrosive paint
CN118325453A
Photo-thermal self-healing ice-resistant coating material as well as preparation method and application thereof
CN118580767A
Preparation method of transparent self-repairing polydimethylsiloxane elastomer material and preparation method of flexible sensor
CN118667165A
Preparation method of SA-alpha-ZrP / PPDA / PDMS self-cleaning heat-conducting anticorrosive paint
CN118834598A
Cited By
Device and method for evaluating separation performance of ion exchange membrane based on electrochemical impedance spectroscopy
CN120891056A